The Implementation of “wordwall” web-based games as instructional media to improve Arabic vocabulary mastery of 8th grade students at SMP Nurul Huda Modung - Fera Andriani Djakfar Musthafa; Hoirul Anam (Aqlamuna: Journal of Educational Studies, 2023)
In digital era, learning is not enough just to be carried out with conventional media. Today's students are close to various applications and websites, so it is necessary to apply them in the learning process. One of the innovative instructional media today is an educational web-based game named “Wordwall”. This application is a learning web-based game in which there are many types of games that students can play. This study aims to find out how to learn Arabic vocabulary using the web-based game "Wordwall" and what are the advantages and disadvantages of "Wordwall" in learning Arabic vocabulary for eighth graders at Nurul Huda Junior High School. Modung District, Bangkalan Region. The methodology in this research is descriptive qualitative, to describe the conditions of the research subjects and reveal the facts in the field. This research took place at Nurul Huda Junior High School Modung, Bangkalan Region, specifically eighth graders. The method of data collection was by interview, observation and documentation. As the results, this educational game brings many advantages, and disadvantages as well. The advantages are: the students can study enthusiastically and happily, because they can play and learn a lot of new vocabulary at the same time. This web-based game is also flexible; it can be used by students of any level. On the other hand, there are also disadvantages of “Wordwall”. Among them are: for basic users, there are only 5 game templates. If you want more, users have to pay 54,000 rupiah per month. The drawback of a free account is that sometimes the font changes suddenly and sometimes errors occur. Besides those things, learning takes a very long time online, and it requires a lot of internet quota.